Characterization of the divalent metal binding site of bacterial polysaccharide deacetylase using crystallography and quantum chemical calculations. Issue 7 (15th January 2014) - Munan Shaik, Md; Bhattacharjee, Nicholus; Bhattacharjee, Anirban; Field, Martin J.; Zanotti, Giuseppe
ABSTRACT Peptidoglycan deacetlyase (HP0310, HpPgdA) from the gram‐negative pathogen Helicobacter pylori, is the enzyme responsible for a peptidoglycan modification that counteracts the host immune response. In a recent study, we determined the crystallographic structure of the enzyme, which is a homo‐tetramer (Shaik et al., PloS One 2011;6:e19207). The metal‐binding site, which is essential for the enzyme's catalytic activity, is visible within the structure, but we were unable to identify the nature of the metal itself. In this study, we have obtained a higher‐resolution crystal structure of the enzyme, which shows that the ion bound is, in fact, zinc. Analysis of the structure of the four sites, one per monomer, and quantum chemical calculations of models of the site in the presence of different divalent metal ions show an intrinsic preference for zinc, but also significant flexibility of the site so that binding of other ions can eventually occur. Proteins 2014; 82:1311–1318. © 2013 Wiley Periodicals, Inc.